Improving Teacher's Ability to Understand Gender Equality in the Mathematics Learning through Academic Supervision in Vocational High School - Putra, Syalendra; Badeni, Badeni; Haji, Saleh (Yayasan Corolla Education Centre, 2022)
Through academic supervision, the goal of the study was to determine the rising involvement of teachers in comprehending gender equality in the mathematics learning process at SMK Negeri 6 Seluma. School action research is the sort of study. Teacher observation and student questionnaires are two methods for gathering data. According to the findings of the study, academic supervision can help teachers better comprehend gender equality in the mathematics learning process.